2017
DOI: 10.1016/j.apenergy.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of combustion and emissions of kerosene (RP-3), kerosene-pentanol blends and diesel in a compression ignition engine

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk Chen LF, Ding SR, Liu HY, Lu YJ, Li YF, Roskilly AP. Comparative study of combustion and emissions of kerosene (RP-3), kerosene-pentanol blends and diesel in a compression ignition engine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(29 citation statements)
references
References 42 publications
(49 reference statements)
0
29
0
Order By: Relevance
“…At high engine loads, more fuel was injected which resulted in longer diffusion combustion during, while there was poorer fuel-air mixing than with premixed combustion, leading to higher local equivalence ratio; therefore, a higher absolute mass of particles was produced at higher engine loads [49], for both the fuel sets and at both the timing conditions ( Figure 21 and Figure 22).…”
Section: Particulate Mass Analysismentioning
confidence: 99%
“…At high engine loads, more fuel was injected which resulted in longer diffusion combustion during, while there was poorer fuel-air mixing than with premixed combustion, leading to higher local equivalence ratio; therefore, a higher absolute mass of particles was produced at higher engine loads [49], for both the fuel sets and at both the timing conditions ( Figure 21 and Figure 22).…”
Section: Particulate Mass Analysismentioning
confidence: 99%
“…The properties of RP-3 kerosene are shown in tab. 2 [18]. Injection laws for different injection parameters are shown in fig.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…They reported that the IDT decrease with increased ambient pressure and equivalence ratio. Chen et al [18] conducted a comparative study of diesel and RP-3 kerosene combustion in a compression ignition engine. They found that RP-3 improves the indicated thermal efficiency and reduces fuel consumption in comparison with diesel.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 presents the properties of biodiesel from waste cooking oil, renewable diesel, ULSD, diesel + and Jet A. Jet A is characterized by lower viscosity, distillation temperature range, and cetane number as regards ULSD fuel; the lower density, viscosity, and surface tension cause its better atomization when compared to diesel fuel [20].…”
Section: Fuels and Testsmentioning
confidence: 99%
“…Llamas et al [19] used Jet A1 that was blended with bio kerosene; their investigations concluded that biodiesel could be used to partially substitute fossil jet fuels. Chen et al [20] investigated the emissions from a single cylinder diesel engine that was fueled with kerosene. Such a fuel improved the indicated thermal efficiency and reduced the soot emissions; nitrogen oxide emissions did not have a relevant variation.…”
Section: Introductionmentioning
confidence: 99%